2016
DOI: 10.1002/chem.201601114
|View full text |Cite
|
Sign up to set email alerts
|

Carboxylation of Phenols with CO2 at Atmospheric Pressure

Abstract: A convenient and efficient method for the ortho-carboxylation of phenols under atmospheric CO2 pressure has been developed. This method provides an alternative to the previously reported Kolbe-Schmitt method, which requires very high pressures of CO2 . The addition of a trisubstituted phenol has proved essential for the successful carboxylation of phenols with CO2 at standard atmospheric pressure, allowing the efficient preparation of a broad variety of salicylic acids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(41 citation statements)
references
References 77 publications
(8 reference statements)
0
40
0
Order By: Relevance
“…[25] They found that the use of 2,4,6-trimethylphenol( XI)a sr eaction mediator greatlye nhances the reactivity of the system, avoiding the high pressures commonly required in this kind of phenol carboxylation. [25] They found that the use of 2,4,6-trimethylphenol( XI)a sr eaction mediator greatlye nhances the reactivity of the system, avoiding the high pressures commonly required in this kind of phenol carboxylation.…”
Section: Carboxylation Of C(sp 2 )Aromatic Substratesmentioning
confidence: 99%
See 2 more Smart Citations
“…[25] They found that the use of 2,4,6-trimethylphenol( XI)a sr eaction mediator greatlye nhances the reactivity of the system, avoiding the high pressures commonly required in this kind of phenol carboxylation. [25] They found that the use of 2,4,6-trimethylphenol( XI)a sr eaction mediator greatlye nhances the reactivity of the system, avoiding the high pressures commonly required in this kind of phenol carboxylation.…”
Section: Carboxylation Of C(sp 2 )Aromatic Substratesmentioning
confidence: 99%
“…Phenol and other aromatic alcohols are efficiently carboxylated in ortho positionb yu sing 4equivalents of NaH (X)u nder Scheme11. [25] Scheme10. [24] Scheme12.…”
Section: Carboxylation Of C(sp 2 )Aromatic Substratesmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2016, the Larrosa group developed the first protocol for Kolbe–Schmitt‐type carboxylations that occur efficiently under an atmospheric pressure of CO 2 12. The use of NaH as the base avoided the undesired formation of H 2 O, and allowed the reaction to proceed in a one‐pot process without isolation of the phenoxide precursor.…”
Section: Introductionmentioning
confidence: 99%
“…) in DMF (N, N-dimethylformamide) (2.0 mL) at 150°C for 20 h, and the desired product 12-phenylisoindolo [2,1-b] isoquinoline-5,7-dione (2 a) was obtained in 33% yield ( Table 1, entry 1). The effect of catalysts was firstly investigated, which revealed that Pd(OAc) 2 was the most effective catalyst (36%, entries [1][2][3][4]. No product was observed in the absence of catalyst or base (entries [5][6].…”
mentioning
confidence: 99%